Long-Term Survival of Combined Hepatocellular-Cholangiocarcinoma: A Nationwide Study. (19th July 2021) - Chen, Po-Da; Chen, Li-Ju; Chang, Yao-Jen; Chang, Yun-Jau
Abstract: Background: Combined hepatocellular-cholangiocarcinoma (HCC-CC) is an aggressive primary liver cancer. However, the clinical features are not clearly understood because of limited literature and the complex nature of both hepatocellular carcinoma (HCC) and cholangiocarcinoma (CC). Methods: The records of 100, 754 patients with newly diagnosed liver cancer between 2004 and 2013 were obtained from the Taiwan Cancer Registry. The primary outcome measures were overall survival and local recurrence-free survival. The median follow-up time was 60 months (29–120 months). Results: HCC-CC tended to share some characteristics with HCC, including increased frequency of stage I cases, high individual tumor rates, and similar patterns of viral hepatitis B and hepatitis C infections. In contrast, HCC-CC showed malignant behavior similar to that of CC, as high-grade tumor cell differentiation and presentation of jaundice were predominant in HCC-CC and CC compared with HCC. Overall survival and local recurrence-free survival rates of HCC-CC were between HCC and CC rates. The mortality rate of HCC-CC was 79.2% (HCC, 77.5%; CC, 93.5%) and the local recurrence rate of HCC-CC was 65.3% (HCC, 74.6%; CC, 88.4%). Surgical treatment was an independent factor for the long-term prognosis of HCC-CC, whereas transarterial chemoembolization (TAcE) promoted survival in both surgical and nonsurgical groups. Conclusion: Our data confirmed that, although it reflects the malignant behavior of CC, HCC-CC should mainly be characterized as a subtype of HCC. With careful selection of patients, curative resection and TAcE might benefit the survival of patients with HCC-CC. Implications for Practice: Combined hepatocellular-cholangiocarcinoma (HCC-CC) is a rare cancer that shares demographic characteristics, as well as survival probabilities, with both hepatocellular carcinoma and cholangiocarcinoma. It occurs frequently in patients with hepatitis B virus infection, cirrhotic liver background, and early-stage disease. Compared with 20% of initial resection rates of its counterparts, HCC-CC has higher initial resection rate (55%). Although short-term overall survival is inferior to HCC, its long-term overall survival is similar with HCC. Abstract : This article analyzes population-based data of a study that aimed to determine the clinical prognosis of and to address the lack of comprehensive information on combined hepatocellular-cholangiocarcinoma.